The Effect of Using Guided Writing Procedure Strategy on Students’ Ability in Writing Descriptive Text - Maria Olva; Irwan Susandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This research aims to investigate the effect of using Guided Writing Procedure Strategy on Students’ Ability in Writing Descriptive Text at State Senior High School 2 Benai of Kuantan Singingi Regency. This research was an experimental research with quasi-experimental design by using pretest-post-test. The subjects was the tenth grade. It was a class experimental (X A), and it was a class control (X B). The technique used to collect data was a test. The type of the test was written test. In analyzing the data, the researcher used independent simple t-test and paired sample t-test by using SPSS 16.0 version. Then, the researcher used eta square formula to find out the effect of mystery strategy. Based the result, it showed that to score is 2.07 <16.462>2.82. Then the effect size was 0.91, therefore the researcher can conclude that there was a large effect obtained from students’ ability in writing descriptive text at State Senior High School 2 Benai of Kuantan Singingi Regency